2019
DOI: 10.32604/jrm.2019.07839
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Performance of CFRP-Bamboo Scrimber Composite Beams

Abstract: This study presents a new structure made up of bamboo scrimber and carbon fiber reinforced polymer (CFRP) to address the low stiffness and strength of bamboo scrimbers. Three-point bending test and finite element model were conducted to study the failure mode, strain-displacement relationship, load-displacement relationship and relationships between strain distribution, contact pressure and deflection, and adhesive debonding. The results indicated that the flexural modulus and static flexural strength of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The mechanical properties of the material reinforced with FRP are generally significantly improved [100][101][102]. In order to solve the problem of low bending strength and stiffness of BS, Wu et al [83] studied the CFRP-BS composite beam. It is found that the CFRP sheet effectively improves the bending modulus and static bending strength of the composite beam, and the failure mode is no longer the fracture failure of the bottom fiber, but the bond failure between CFRP and BS.…”
Section: Bendingmentioning
confidence: 99%
“…The mechanical properties of the material reinforced with FRP are generally significantly improved [100][101][102]. In order to solve the problem of low bending strength and stiffness of BS, Wu et al [83] studied the CFRP-BS composite beam. It is found that the CFRP sheet effectively improves the bending modulus and static bending strength of the composite beam, and the failure mode is no longer the fracture failure of the bottom fiber, but the bond failure between CFRP and BS.…”
Section: Bendingmentioning
confidence: 99%
“…The parameters of the cohesive zone model is shown in Table 5, accord to Papers by Wu et al (2020Wu et al ( , 2019. The thickness of adhesive was 0.1 mm.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…With the invention of bamboo composites, such as laminated bamboo lumber [82][83][84][85][86][87], glubam [88][89][90][91][92], parallel strand bamboo [93][94][95][96][97], and their combinations with AFRP, CFRP [98,99], and other materials, the possibility of using bamboo as reinforcement for concrete is significantly expanding. Multiple studies have been done on new types of bamboo-based and concrete composites, such as engineered bamboo-concrete sandwich panels, bamboo particle concrete, bamboo fibre concrete, bamboo tube grid concrete panels, etc., showing wide possibilities of utilization of bamboo variations in composites with concrete [100,101].…”
Section: Potential Of Brc Beams In Structural Applicationmentioning
confidence: 99%